THE SUBSTITUTION OF LEMURU FISH WASTE IN THE STUDY OF MAKING NATA DE FISH - Adharani, Nadya; Rachmawati, Nandya F; Sartika, Dewi; Winata, Widhi Sakti (Politeknik Kelautan dan Perikanan Sidoarjo, 2023)
Nata is the result of fermentation products by Avetobacter xylinum. If nata de coco is often found with coconut water media, then nata de fish is made with unused lemuru stew media and has the potential to be waste because it results in polluting the environment. This study aims to find out how to make nata by comparing the substitution of lemuru decoction to the quality of nata de fish. The study used factorial RAL with two factors, namely the use of clean water 1.5 L and 2 L, the results of the analysis on each parameter including, the interaction of treatment had a very real effect (p < 00.1) on thickness. Treatment interactions had a very real effect (p < 0.01) on the amendment. Treatment interactions had a very real effect (p > 0.01) on wet weight. Treatment interactions had a very noticeable effect (p > 0.01) on protein levels. The test results of the presence of Esecherichia coli in each treatment showed an average < 3 MPN/g.